2011
DOI: 10.1007/s11104-011-0783-1
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback between acidification and organic phosphate mineralization in the rhizosphere of maize (Zea mays L.)

Abstract: To test the hypothesis that rhizosphere acidification would enhance the hydrolyzation of organic phosphates by increasing phosphatase activity. A Petri dish experiment with sterile agar and a pot experiment with a low P soil were used. In the Petri dish experiment, roots of each plant were cultured in two compartments, each of which contained agar with one of three nitrogen combinations: NH 4 + /N0 (N0 = nitrogen free), NH 4 + /NO 3 -, and NO 3 -/N0. Phytin was supplied as the sole phosphorus (P) source to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
2
12
1
Order By: Relevance
“…These results showed that the added phytin was utilized by maize, while the plant P uptake was not affected by different N forms. It was different from a previous study that plant P uptake of maize was increased by the application of NH 4 + compared to NO 3 − (Ding et al 2011). These different results suggested that the effect of pH regulation on plant P uptake in the sterile condition was not consistent with the plant-AM fungus-PSB system.…”
Section: Plant P Uptake From Phytin Affected By Different N Formscontrasting
confidence: 88%
See 3 more Smart Citations
“…These results showed that the added phytin was utilized by maize, while the plant P uptake was not affected by different N forms. It was different from a previous study that plant P uptake of maize was increased by the application of NH 4 + compared to NO 3 − (Ding et al 2011). These different results suggested that the effect of pH regulation on plant P uptake in the sterile condition was not consistent with the plant-AM fungus-PSB system.…”
Section: Plant P Uptake From Phytin Affected By Different N Formscontrasting
confidence: 88%
“…The soil in this system was supplied with different N forms (NH 4 + and NO 3 − ). Previous studies (Li et al 1991;Ding et al 2011) reported that the addition of different N forms can decrease or increase soil pH in the rhizosphere and hyphosphere (the volume of soil influenced by the AM fungal hyphae, see Jansa et al 2013). We hypothesized that the bioavailability of organic P (phytin) and phosphatase activity from the root and/or PSB in the rhizosphere and hyphosphere increase under low pH mediated by NH 4 + fertilizer.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Plants could change the rhizosphere pH by 1–2 units (Nye 1981). For example, plants release protons when they absorb NH 4 + , which could result in the reduction of pH (Ding et al 2011). Lu et al (2007) found that mangrove roots could release low-molecular-weight organic acids that resulted in the reduction of pH by 0.2–0.5 units in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%